2006
DOI: 10.1128/mcb.00384-06
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 Promotes and Enhances Skeletal Muscle Differentiation

Abstract: Transforming growth factor ␤1 (TGF-␤1) and myostatin signaling, mediated by the same Smad downstream effectors, potently repress skeletal muscle cell differentiation. Smad7 inhibits these cytokine signaling pathways. The role of Smad7 during skeletal muscle cell differentiation was assessed. In these studies, we document that increased expression of Smad7 abrogates myostatin-but not TGF-␤1-mediated repression of myogenesis. Further, constitutive expression of exogenous Smad7 potently enhanced skeletal muscle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 58 publications
6
78
0
7
Order By: Relevance
“…16,17 More recently, there have been reports revealing some direct action of myostatin on the myogenic factors. 18,19 In the current study, we did show that the inhibition of myostatin expression by antisense RNAs elevated the level of MyoD expression at the mRNA level in vivo. Thus, our results elucidate a possible mechanism for targeting the myostatin gene for potential treatment of the muscle wasting diseases and provide further evidence that myostatin regulates the muscle growth through the MyoD pathways.…”
Section: Antisense Inhibition Of Myostatin C-m Liu Et Almentioning
confidence: 72%
“…16,17 More recently, there have been reports revealing some direct action of myostatin on the myogenic factors. 18,19 In the current study, we did show that the inhibition of myostatin expression by antisense RNAs elevated the level of MyoD expression at the mRNA level in vivo. Thus, our results elucidate a possible mechanism for targeting the myostatin gene for potential treatment of the muscle wasting diseases and provide further evidence that myostatin regulates the muscle growth through the MyoD pathways.…”
Section: Antisense Inhibition Of Myostatin C-m Liu Et Almentioning
confidence: 72%
“…These processes were associated with the upregulation of the expression of Smad3 and 4, and the phosphorylation of Smad2 and 3, as expected from a member of the TGF-b family that signals through this pathway (Zhu et al 2004, Kollias et al 2006). An antifibrotic process was simultaneously elicited, as evidenced by the stimulation of the expression of a) the myostatin activity inhibitor, follistatin (Hill et al 2002, Amthor et al 2004, Kocamis et al 2004, b) a Smad signaling inhibitor, Smad7 (Forbes et al 2006), and c) a collagen breakdown inducer, matrix metalloproteinase 8 (MMP-8;Siller-Lopez et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to occur via the Smad pathway, since myostatin signals through Smad2-4, and phosphorylates Smad3 (Zhu et al 2004). In addition, it triggers a feedback compensatory mechanism through the inhibitory Smad7 that inactivates myostatin promoter, and counteracts myostatin and TGF-b action (Zhu et al 2004, Forbes et al 2006, Kollias et al 2006. In turn, Smad2-4 upregulate myostatin expression by activating its promoter (Zhu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We first determined the effects of Coco on the differentiation of C2C12 cells to myoblasts, a process that is inhibited by TGFβ1 (Kollias et al, 2006). We found that C2C12 cells transfected with a Coco siRNA have a twofold higher rate of myoblast differentiation, as determined by myogenin immunostaining, compared with cells transfected with a control siRNA (Fig.…”
Section: Interaction Between Coco and Tgfβ1 Modulates Cell Fate Decismentioning
confidence: 99%